Conventional Financial Performance, Economic Value Added, Human Economic Value Added, Value Added Intellectual Coefficient And Its Impact On Stock Return Of Companies Operating In Energy Sector In Indonesia And Malaysia - Anton Wijaya (Ilomata International Journal of Tax and Accounting, 2021)
Return is one of the factors that investors pay attention in determining their investment policies. For this reason, this study analyzes the effect of several conventional financial performance indicators such as total asset turnover, current assets, debt to equity ratio, and return on assets to stock returns. Other variables that are seen as new indicators such as economic value added, human economic value added, and value added intellectual capital are also examined for their effects on stock returns. Companies engaged in the energy sector in Indonesia and Malaysia were made as objects in this study. OLS regression is used to analyze the effect of independent variables on the dependent variable. The results of an analysis of energy company data in Indonesia show that debt to equity ratio and human economic value added have a negative and significant effect on stock returns, while economic value added and value added intellectual capital have a positive and significant effect on stock returns. As for the object of research on energy companies in Malaysia, the results showed that total asset turnover, economic value added and value added intellectual capital had a positive and significant effect on stock returns.